2023
DOI: 10.3390/su15075643
|View full text |Cite
|
Sign up to set email alerts
|

Non-Monotonic Relationship between Corporate Governance and Banks’ Operating Performance—The Moderating Role of CEO Duality: Evidence from Selected Countries

Abstract: This study examines the non-monotonic (U-shaped, inverted U-shaped or curvilinear) relationship between the corporate governance (CG) and bank performance of commercial banks operating across four countries whose CG framework is based on the OECD principals of CG. Using a dataset of 4230 bank-years observation from 2012–2021, the study shows that governance–performance relations may be non-monotonic but not U-shaped using a two-line approach and the Robin Hood algorithm. In addition, this study, using feasible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
1
0
0
Order By: Relevance
“…Moreover, there is strong relationship between corporate governance and banking institutions performance. The findings of current research are in line with the findings of current research as strong governance procedure leads towards batter performance of the financial institutions (Amrani & Najab, 2023;Boachie, 2023;Enam et al, 2023). In this connection, according to the findings of Mamatzakis et al (2023) the strong governance procedures leads toward batter performance of banking institutions.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, there is strong relationship between corporate governance and banking institutions performance. The findings of current research are in line with the findings of current research as strong governance procedure leads towards batter performance of the financial institutions (Amrani & Najab, 2023;Boachie, 2023;Enam et al, 2023). In this connection, according to the findings of Mamatzakis et al (2023) the strong governance procedures leads toward batter performance of banking institutions.…”
Section: Discussionsupporting
confidence: 87%
“…The representative's responsibility is to maximise the principal's profits while keeping their welfare in mind. This challenge, however, can lead to an agency conflict as the representative's preferences may not always align with those of the principal, a phenomenon referred to as an imbalance of concern (Enam et al, 2023). Considering these claims, this study affirms that conflict of interest opposes corporate governance doctrines.…”
Section: Effects Of Egocentric Leadership On Corporate Governance And...supporting
confidence: 54%
“…This author found that corporate governance is positively related to organisational financial performance. Enam et al (2023) investigated the non-monotonic relationship between corporate governance and banks' operating performance. They found that the relationship between corporate governance and performance was nonlinear, which means that corporate governance had a moderate impact on the performance of banks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations